PELAKSANAAN PERATURAN DAERAH KABUPATEN SUKOHARJO NOMOR 7 TAHUN 2017 TENTANG PENATAAN DAN PEMBINAAN PASAR RAKYAT, PUSAT PERBELANJAAN DAN TOKO SWALAYAN DI KECAMATAN TAWANGSARI - DEWI, AYU SARTIKA PUTRIANA (Dinamika Hukum, 2020)
This study aims to review and analyze the Structuring and Development of People's Markets, Shopping Centers and Supermarkets based on Regional Regulations of Sukoharjo District Number 7 of 2017 and analyze the Obstacles to Structuring and Guiding of Public Markets, Shopping Centers and Supermarkets based on Regional Regulations of Sukoharjo District Number 7 of 2017 . This research is a type of empirical / sociological legal research and when viewed from the nature of the study, including descriptive research. Research Locations in the Sukoharjo Regency Cooperative and SME Office. Data Types used include primary data and secondary data. Data collection techniques used were interviews, literature studies including legislation, books, journals, and other documents that are relevant and related to the writing of this law. Data analysis uses qualitative data analysis. The results of this study indicate that the implementation of Sukoharjo regency number 7 of 2017 concerning structuring and fostering people's markets, shopping centers and supermarkets in Tawangsari District has been going well with the fulfillment of aspects of legal substance in the form of a set of rules governing the structuring and fostering of public markets, central shopping and supermarkets, aspects of the legal structure with the formation of organizational structures and structures in the Sukoharjo Regency SME Cooperative Service and the fulfillment of legal culture aspects that involve the role of law enforcement officials in structuring and fostering public markets, shopping centers and supermarkets and still having obstacles in structuring and fostering people's markets, shopping centers and supermarkets in the form of setting the distance between people's markets, shopping centers and supermarkets. Keywords: structuring, fostering, people's markets, shopping centers and supermarkets, law enforcement, barriers